Eccentric finger joint movements for different grip types in sport climbing - Fischer, G.; Schweizer, A.; Wolf, P.; Farr, A.; Calcagni, M.; Reissner, L. (Sports Biomechanics, 2026)
Eccentric finger movements have been identified as risk factor in the injury mechanism of pulley ruptures during climbing. So far, they have mainly been associated with inadvertent events. Whether eccentric movements also occur as regular motion patterns was not assessed. Main purpose of this study was to examine eccentric finger movements during typical climbing tasks. Therefore, kinematics and interaction force of eleven elite climbers was recorded during a sequence of four climbing moves. Participants were instructed to use crimp, half-crimp, open-hand grip and campusing. Change of flexion angle in the proximal interphalangeal (PIP) joints from the start to the end of the holding phase (deltaPIPP2) was calculated. Mean deltaPIPP2 was -1.5° (SD 6.6°), 0.2° (5.1°), -2.9° (3.4°) and -6.0° (9.6°) for the open-hand, half-crimp, crimp and campusing task, respectively, whereby negative values represent eccentric movements. Eccentric finger joint movements (deltaPIPP2 < 0°) during the holding phase were very common (59-73%) across all grip types. The loading rate was highest during campusing and lowest using the crimp grip. Climbers exhibit eccentric finger movements not only during accidental slips or when fatigued, but also as consistent patterns. Further research is needed to assess whether these differences are associated with an individual`s risk of pulley injury.